Pengaturan dan Kewenangan Polisi Pamong Praja dalam Upaya Penanggulangan Gelandangan dan Penduduk Pendatang di Kabupaten Badung - I Made Angga Wira Nugraha (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The linkage between the Civil Service Police Unit officers with appropriate agencies whose activities have a close connection in creating a conducive environment between local government and the people can perform activities in a safe, peaceful, orderly and applicable in areas with motivating people to create the rule of law. This needs to be pursued so that the police authority of the civil service as a law enforcement officer in fostering peace and order will be based on the activities and supervision of extension, no longer be a matter of the sanctions, penalties or fines. Be aware that in creating an orderly and safe condition, not just the responsibility of the Municipal Police alone, but public participation is crucial the achievement of order and peace. Given the number of homeless and migrants who are not registered in the registry office or the competent authority, in addition to the lack of government attention to the homeless, so the implication raises public order and public tranquility be disturbed. Principal issues to be addressed in this study is the First, the setting and the authority of the Municipal Police and the Homeless curb migrants in Badung, and constraints faced in the Municipal Police enforcing rules on homeless and migrants. This study is the approach taken by the normative approach to law (statute approach), approaches the concept (conceptual research), case-based approach (case approach) the nonnative analysis shows that the police authority of the civil service is based on the principles of the law, the nonns applicable law, whereas the juridical conceptual analysis regarding the effectiveness of law enforcement. Based on the results of the discussion, setting and Municipal Police Authority in carrying out duties and discipline Homeless Population entrants subject to the provisions of Law No. 32 of 2004, and regulations Badung District No. 4 of 2001 on public order. Constraints faced by local governments in the enforcement of rules against bums and penduduku immigrants are human resource constraints the police civil service itself is still not professional and legal culture of society that still considers the work is still a beggar or bum culture.